Chronic appendicitis in an 11-year-old pediatric patient: a case report - G. Ramirez, Cesar I.; T. Ordaz, David E.; L. Lugo, Leonel; U. Ramos, David G. (International Journal of Research in Medical Sciences, 2024)
Chronic appendicitis is a very little-known entity within the segment of acute abdominal pain as an abdominal symptom, going unnoticed by a low grade of suspicion as well as by its very varied representation, the case of a pediatric patient is presented, with all its natural history of the disease, approach and conclusion to resume the importance of its search in clinical practice.